2013
DOI: 10.1186/2043-9113-3-22
|View full text |Cite
|
Sign up to set email alerts
|

PROGgene: gene expression based survival analysis web application for multiple cancers

Abstract: BackgroundIdentification of prognostic mRNA biomarkers has been done for various cancer types. The data that are published from such studies are archived in public repositories. There are hundreds of such datasets available for multiple cancer types in public repositories. Wealth of such data can be utilized to study prognostic implications of mRNA in different cancers as well as in different populations or subtypes of same cancer.DescriptionWe have created a web application that can be used for studying progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 20 publications
3
117
0
Order By: Relevance
“…In contrast, TMEPAI acts as a tumor suppressor in prostate cancer (8,9). To find out the effects of TMEPAI on the survival of patients with MM, a fetal hematological malignancy, we analyzed the PROGgene database from http://watson.compbio.iupui.edu/chirayu/p roggene/database/index.php (20), which curates a large size of reported data on various cancer genes and associated patient survival. There was one confirmative dataset (GSE2658) (21) regarding the prognostic value of TMEPAI expression and MM patients.…”
Section: Overexpression Of Tmepai Induces MM Cell Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, TMEPAI acts as a tumor suppressor in prostate cancer (8,9). To find out the effects of TMEPAI on the survival of patients with MM, a fetal hematological malignancy, we analyzed the PROGgene database from http://watson.compbio.iupui.edu/chirayu/p roggene/database/index.php (20), which curates a large size of reported data on various cancer genes and associated patient survival. There was one confirmative dataset (GSE2658) (21) regarding the prognostic value of TMEPAI expression and MM patients.…”
Section: Overexpression Of Tmepai Induces MM Cell Apoptosismentioning
confidence: 99%
“…The association of TMEPAI expression with the overall survival of MM patients was analyzed using the PROGgene database (http://watson.compbio.iupui.edu/chirayu/ proggene/database/index.php) (20). The TMEPAI expression profile was analyzed using the DNA microarray on the typical 60 cancer cell lines from National Cancer Institute (NCI 60-cell line) (https://www.ncbi.nlm.nih.gov/sites/GDSb rowser?acc=GDS4296).…”
Section: Tmepai Analyses Based On the Public Gene Expression Databasesmentioning
confidence: 99%
“…The results were obtained using R package 'survival' and 'survAUC'. 6 The GIANT provides grouped variable selection methods (least absolute shrinkage and selection operator; LASSO, Elastic Net Regularization; Elastic Net, Network-Regularized high-dimensional Cox-regression; Net) by using 'coxnet' package in R. In the Net analysis, we transformed the topologic pathway information of large databases (KEGG, Biocarta, HumanCyc, Reactome, Panther, and NCI) into a gene network matrix by using 'graphite' in R. Users can set the mixing parameter α, which decides the balance between LASSO and Ridge regression. All grouped variable selection used "leave-one-out" method for crossvalidation.…”
Section: Significant Genes Of Specific Cancermentioning
confidence: 99%
“…For instance, SurvExpress, PROGgene, and PrognoScan provide statistical prognostic significance by using mRNA expression data [5][6][7]. However, the survival analysis results are prone to be associated with following limitations: (1) the tools use mRNA expression as a simple categorical value to provide Kaplan-Meier curve in all patients regardless of their characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the detection of the expression of a single gene does not effectively characterize the expression of a gene cluster composed of tens or hundreds of genes. It has been demonstrated that prognostic information from multi-gene signatures, including network modules, can reduce the heterogeneity of diseases with greater accuracy than data of a single gene (6). For example, a classifying system for breast cancer profiles was constructed based on 70 genes in a study by van de Vijver et al (7).…”
Section: Introductionmentioning
confidence: 99%